2017
DOI: 10.1002/adv.21817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effective forcespinning parameters controlling polyvinyl alcohol nanofibers diameter using artificial neural network

Abstract: In this research, the polyvinyl alcohol (PVA) nanofibers through forcespinning process were successfully produced and the effective parameters for predicting nanofibers diameter using artificial neural network (ANN) were investigated. The various parameters of forcespinning process including rotational speed, orifice, distance to the collector, and polymer concentration were designed to produce PVA nanofibers.Scanning electron microscopy (SEM) showed that the produced fibers diameter was in the range of 0.56-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Fiber size distribution and morphology play a significant role in the porosity, the surface to volume ratio, functionality, and performance. 13 The shape, diameter of the electrospun nanofibers, and spatial distribution have a close relationship with their functional performance and can be divided into four categories: polymer properties (molecular weight and solubility), properties of the working fluids (the concentration, solution viscosity, dielectric properties, surface tension, and conductivity), the operational conditions (applied voltage, the fluid flow rate, nozzle–collector distance, and nozzle diameter of the spinneret), and manipulation of the environmental conditions (temperature, atmospheric pressure, relative humidity, the possible vacuum and even hot air blowing). These parameters have a positive impact on downsizing of the nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber size distribution and morphology play a significant role in the porosity, the surface to volume ratio, functionality, and performance. 13 The shape, diameter of the electrospun nanofibers, and spatial distribution have a close relationship with their functional performance and can be divided into four categories: polymer properties (molecular weight and solubility), properties of the working fluids (the concentration, solution viscosity, dielectric properties, surface tension, and conductivity), the operational conditions (applied voltage, the fluid flow rate, nozzle–collector distance, and nozzle diameter of the spinneret), and manipulation of the environmental conditions (temperature, atmospheric pressure, relative humidity, the possible vacuum and even hot air blowing). These parameters have a positive impact on downsizing of the nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…The diameters of fibers were 0.7-1.5 µm for 20% PVA and 0.5-1.1 µm for 16% PVA solutions. When compared to other studies, standard forcespinning devices use significantly less-concentrated PVA solutions (6 to 12 wt.%) to prepare fiber layers of similar quality [46,47]. The spinning devices used in previously mentioned studies showed technological limitations to applicable concentrations of the spun polymeric solution, which was not an issue for the instrument used in this paper.…”
Section: Discussionmentioning
confidence: 91%
“…The movement of fibers to the collector along a spiral trajectory is similar to the case of Figure 1a. The main parameters that affect the fibers themselves and the final formation thereof comprise the viscosity, the surface tension of the used solution, the temperature, the evaporation rate, the centrifugal speed of the spinneret and the distance between the fiber and the collector [41,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…In an ice-bath, W 1 and O were emulsified using a high-speed homogenizer at 12 000 rpm (Ultra-Turrax TP 18/10, IKA, Germany) for 2 min to form a primary emulsion. Then, the primary emulsion was injected into 40 mL of 1% PVA solution , (W 2 ) and homogenized at 8000 rpm (Ultra-Turrax TP 18/10, IKA, Germany) for 3 min to obtain the double emulsion. Finally, 80 mL of 3% NaAc solution as a diluent was added to the double emulsion, magnetically stirred at 20 °C for 2 h washed with 10 mL of purified water each time for three times, and lyophilized.…”
Section: Methodsmentioning
confidence: 99%